Breast implant-associated squamous cell carcinoma in a male patient: A case report and review of the medical literature - Xia, Zihuan; Han, Bing; Wang, Lei; Ning, Guansen; Guo, Zongke; Zhang, Jue; Yu, Bing; Chen, Ming; Zhang, Wanxing; Wang, Ke; Ma, Xiaojun (Frontiers in Surgery, 2023)
Background: Primary squamous cell carcinoma (SCC) of the breast is a rare tumor type. The diagnosis of this tumor type is more frequently made only after microscopy evaluation. Breast implant-associated SCC is rarer with medical literature review indicating only 18 cases reported in female individuals. Case Presentation: We reported an unusual case that a man found a 3-cm sized mass on his left breast at first, who had a implant surgery 18 years previously to reconstruct the deformed left breast, as related to the Poland's syndrome. More than 1 year after the mass was detected, the size of the mass gradually increased to 20 cm with swelling and severe pain, and the patient was admitted to our hospital. The patient underwent surgical excision of the tumor, followed by removal of the implant, complete capsulectomy, and sentinel lymph node biopsy. The microscopy evaluation demonstrated the tumor as moderately and poorly differentiated invasive SCC. Follow-up at 12 months after showed multiple metastases, including the skin of the chest, axillary lymph nodes and pleura. Conclusions: Breast implant-associated SCC can occur in male patients. Therefore, it should be considered when the clinical manifestation or histopathological appearance is not typical of other breast neoplasms. Malignant transformation of normal epithelial cells takes about 18 years, after which rapid evolution follows leading to fast growth of the tumor.